Quadro editorial (Estudos em Design, 2026)
EditoresCristina PortugalRita CoutoAvaliadores desta edição V. 34, n. 1 (2026)Adriana GralowAdriana MirandaAdriana Sampaio LeiteAlexandre OliveiraAline SaviÁlvaro SousaAna Beatriz Pereira de AndradeAna BerwangerAna PazminoAndre Batistella SouzaAndré Ribeiro de OliveiraArtur MottinBruno Serviliano FariasCarlo FranzatoCarolina Vaitiekunas PizarroCassia Carrara DomicianoCassia FurtadoChrystianne IvanóskiCláudia SilvaCyntia Malaguti de SousaDaniel RaposoDaniela Estaregue AlvesDoris KosminskyEdson RufinoEkaterina BarcellosEverton da SilvaFabiane FernandesFábio Caparica de LunaFausto MedolaFelipe ViaroFernando FoglianoFrederico BraidaGabriel PatrocinioGisela CamposGuilherme AltmayerGustavo CurcioIgor Ramos Luiza Falcão Soares CunhaLuiz Guilherme Oliveira MarquesMarcio GuimarãesMaria Do Carmo Gonçalves CurtisOlavo NetoOtniel AltamiranoPatrícia BragaPatrícia dos SantosRafaela SarinhoRafaella PeresRavi PassosRenata CadenaRenata WanderleyRogério CamaraRosane MartinsSandra Maria SouzaSérgio Luciano da SilvaSilvia SchnaiderTiago SilvaWalter CorreiaVera DamazioVerônica Freire